Entering, Staying, Shifting, Leaving, and Sometimes Returning: A Descriptive Analysis of the Career Trajectories of Two Cohorts of Alternatively Certified Mathematics Teachers. Issue 9 (September 2021) - Brantlinger, Andrew
Background: By attracting high-achieving college graduates and professional career changers, selective alternative certification programs, such as the New York City Teaching Fellows (NYCTF), promise to address pressing teacher shortages while also improving outcomes in hard-to-staff schools. Purpose: Looking at the main patterns in their careers before, during, and after completing NYCTF, the study provides insights into the short- and long-term impacts of mathematics teachers who entered as first- and second-career teachers on NYC public schools and the people in them. Participants: The study tracked the career trajectories and decision-making of more than 600 NYCTF mathematics teachers over a 9-year period. Research design: The longitudinal analysis of the teachers' career trajectories is illuminated by descriptive statistics and qualitative analyses of their responses to open-ended survey items. Results: The article provides a portrait of urban mathematics teachers' career decision-making as it unfolds over time. It challenges conventional understandings by demonstrating the stochastic nature of teachers' career decision-making and, as part of this, consequential amounts of involuntary and midyear turnover. It further shows that, although in many ways similar, the career trajectories of the career changers and recent college graduates differed in key regards. Recommendations: On their own, strategies designed to attract high-achieving recent graduates and professional career changers to teach core subjects like mathematics will not solve long-standing teacher turnover and shortage issues in in high-needs urban schools. Districts also should focus on retention strategies, including training and induction tailored to meet the different needs and career goals of first- and second-career teachers.